Nutrition Support for Athletic Performance - Parnell, Jill (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Athletes and their support personnel are constantly seeking evidence-informed recommendations to enhance athletic performance during competition and to optimize training-induced adaptations. Accordingly, nutritional and supplementation strategies are commonplace when seeking to achieve these aims, with such practices being implemented before, during, or after competition and/or training in a periodized manner. Performance nutrition is becoming increasingly specialized and needs to consider the diversity of athletes and the nature of the competitions. This Special Issue, Nutrition Support for Athletic Performance, describes recent advances in these areas.